The “No bed syndrome” in Ghana — what, how and why? A literature, electronic and print media review - Yevoo, Linda Lucy; Amarteyfio, Kezia Amerley; Ansah-Antwi, Jewel Afriyie; Wallace, Lauren; Menka, Eunice; Ofori-Ansah, Gifty; Nyampong, Isaac; Mayeden, Samuel; Agyepong, Irene Akua (Frontiers in Health Services, 2023)
Objectives: ‘No bed syndrome’ has become a familiar phrase in Ghana. Yet, it does not currently exist in medical texts or peer reviewed literature as accepted terminology for any defined syndrome. This review aimed to understand what the phrase means in the Ghanaian context, how and why it occurs, and potential solutions. Design: A qualitative desk review using a thematic synthesis of grey and published literature, print and electronic media content covering the period January 2014 to February 2021. Text was coded line by line to identify themes and sub-themes related to the research questions. Analysis was manual and with Microsoft Excel to sort themes. Setting: Ghana Participants and Intervention: Not applicable Results: “No bed syndrome” describes the turning away by hospitals and clinics of people seeking walk in or referral emergency care with the stated reasons “no bed available” or “all beds are full”. There are reported cases of people dying while going round multiple hospitals seeking help. The situation appears to be most acute in the highly urbanized and densely populated Greater Accra region. It is driven by a complex of factors related to context, health systems functions, values, and priorities. The solutions that have been tried are fragmented rather than well-coordinated systems reform. Discussions and recommendations: A holistic review of the state of Ghana’s emergency healthcare system with accompanying formulation, implementation, continuous monitoring and evaluation of holistic policies and programs for systems reform to increase and strength emergency care systems capacity and responsiveness is urgently needed.